DESIGN AND ANALYSIS OF APPROACH TRESTLE - M, Arunrex.; A, Dineshmanickam.; D, Eraianbu.; M, Ramkumar.; S, Subathra. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The present research work examines the operational efficiency of select major ports in in india over the period of time 1993 to 2011 through data envelopment analysis. Hypothesis tested in this study is, size does not determine port efficiency. Based on the results it is found that both bigger ports i.e. Mormugao, Jawaharlal Nehru port Trust and smaller ports Ennore, Tuticorin were proved have efficient port operations all through. Through the result of super-efficient analysis, the study found that JNPT port rated as number one super-efficiency port among the selected major ports in india. Trestle works creating a hierarchical categorization tree that can be used to predict missing attribute values and cluster sets of examples into conceptually meaningful groups. New categorization model is competitive with non-incremental approaches and more closely approximate human performance